Functions of BLM Helicase in Cells: Is It Acting Like a Double-Edged Sword? - Kaur, Ekjot; Agrawal, Ritu; Sengupta, Sagar (Frontiers in Genetics, 2021)
DNA damage repair response is an important biological process involved in maintaining the fidelity of the genome in eukaryotes and prokaryotes. Several proteins that play a key role in this process have been identified. Alterations in these key proteins have been linked to different diseases especially neoplastic transformation leading to cancer. BLM is a 3' - 5' ATP dependent RecQ DNA helicase that is one of the most essential genome stabilizers involved in the regulation of DNA replication, recombination, and both Homologous Recombination and Non-Homologous End Joining pathways of double-strand break repair. BLM structure and functions are known to be conserved across many species like yeast, drosophila, mouse, and human. Genetic mutations in BLM cause a rare, autosomal recessive disorder, Bloom syndrome (BS). BS is a monogenic disease characterized by genomic instability, premature aging, predisposition to cancer, immunodeficiency and pulmonary diseases. Hence these characteristics point towards BLM being a tumor suppressor. However, in addition to mutations, the BLM gene undergoes various types of alterations including an increase in the copy number, transcript, and protein levels in multiple types of cancers. These results along with the fact that the lack of wildtype of BLM in these cancers has been associated with increased sensitivity to chemotherapeutic drugs indicate that BLM also has a pro-oncogenic function. Even though a plethora of studies has reported the effect of BLM gene mutations in various model organisms, there is a dearth in the studies undertaken to investigate the effect of its oncogenic alterations. Here we rationalize and integrate the dual functions of BLM both as a tumor suppressor and maybe as a proto-oncogene, and enlist the plausible mechanisms of its deregulation in cancers.